The origin of sulfur in Canary Island magmas and its implications for Earth’s deep sulfur cycle - Zoltán Taracsák; Margaret E. Hartley; Ray Burgess; Marie Edmonds; Marc-Antoine Longpré; Brian D. Monteleone; Romain Tartèse; Alexandra V. Turchyn (Proceedings of the National Academy of Sciences, 2025)
The global sulfur cycle plays a critical role in the redox evolution of Earth’s surface and upper mantle, yet the distribution and origin of sulfur in the mantle remains largely unconstrained. El Hierro is a volcanic island in the Canary archipelago that is fed by sulfur-rich magmas. To constrain the origin of sulfur in these melts, we combine in situ sulfur isotope analyses with regression modeling. We calculate that undegassed El Hierro melts have δ 34 S values of 0 ± 2‰. The average δ 34 S of undegassed El Hierro melts is 0.3‰ to 1‰ higher than magmas erupting at mid-ocean ridges. Mass balance calculations reveal that El Hierro’s mantle source contains 310 ± 120 μg/g sulfur and that on average 60% of sulfur in the source is of recycled origin. This recycled material should contain >1,800 μg/g sulfur to satisfy isotopic constraints on its mass fraction in the mantle source. The sulfur and oxygen isotopic signature in serpentinites and sediments deviate significantly from the upper mantle, making them unsuitable candidates for the recycled material. An oxidized partial melt of recycled oceanic crust that retained one third of its sulfur budget after subduction zone processing can explain excess sulfur in the Canary Island mantle. Recycled oceanic crust is expected to contain sulfur as sulfide, which is not capable of oxidizing the mantle. The presence of ferric iron in the recycled component is necessary to produce metasomatic melts that are oxidizing enough to carry sufficient sulfur into the mantle source of ocean island basalts.